O discurso de Paulo Freire: seu contributo à educação brasileira - Sérgio Lourenço Simões (EccoS – Revista Científica)
Contribute to specify certain situations analyzed by thinker from. In this paper, we examine the contribution of Freire for the Brazilian education, taking as a starting point his speech signals, denouncing the ¿collapse¿ of education that the working masses was undergoing due to the manipulation Manichean discourse of oligarchic power, disguised as ¿gifts¿ and paternalistic welfare, who seduced and sometimes condemned the ¿ostracism¿ socioeconomic, political and cultural. At the same time, score a few constructions of Freirian verve of neologism, which, in the semantic-conceptual load, contribute to specify certain situations analyzed by the thinker from Pernambuco. These creations support the thesis that Freire did not create words to pleasure, but was to meet a significant unmet need for vocabulary spelling in order to further reading of the world. From this perspective, it points to the semantic rigor of the theoretical and conceptual apparatus in the speech that expresses his sociopolitical and philosophical thought, becomes explicit and discusses how this accuracy is expressed in the written text, establishing the relationship between semantics and pedagogy to explain the expressive charge of his speech.